Refining a software system deployment process model through empirical studies - Panizzi, Marisa Daniela (2023)
Software system deployment describes the activities associated with ensuring that a software system is available for its end users. Every company, regardless of its size, requires an efficient and effective software system deployment process to ensure the customer will accept the system software successfully. Small and Medium Enterprises (SMEs) often operate on limited resources and with strict time constraints and need to improve their processes. For this reason, the existing proposals for deployment processes are not usually useful for SMEs. This fact led us to propose DepProMod (Deployment Process Model) to help SMEs to execute the deployment process of software systems in a systematized and controlled manner. The initial version of DepProMod has subprocesses, activities and tasks defined in addition to a capabilitylevel architecture which allow its implementation in a step-by-step manner, thus adapting to SMEs with different needs and resources. This paper presents the results of two empirical studies carried out to obtain feedback on the model so as to refine it and complete it. Specifically, a case study from an Argentinian level 1 Medium-size software development SME (approximately 55 employees) and the interviews held with two professionals from the software industry are presented. In summary, both empirical studies allowed us to modify, unify and eliminate elements in the model.